RETRACTED: Prevalence, Predictors, and Clinical Presentation of Acute Pericardial Effusion Following Percutaneous Coronary Intervention - Zhao, Bei; Zhang, Jie; Li, Yun; Feng, Xueyao; Mao, Shuai; Yin, Zhao; Liu, Li; Song, Dapeng; Wang, Shouli (Frontiers in Cardiovascular Medicine, 2022)
Background: Iatrogenic pericardial effusion (PE) has been demonstrated to lead to cardiac injury as a sign of systemic inflammatory response. Objectives: This study sought to determine the anatomical characteristics and clinical presentation associated with PE after percutaneous coronary intervention (PCI) by using echocardiography. Methods: The clinical outcomes of all patients with coronary artery disease who underwent PCI from July 2014 to December 2018 were evaluated. The quantitative and qualitative analyses of PE were performed. The associations between the presence of PE and procedural factors were also evaluated. Results: A total of 882 patients were enrolled. PE was found in 144 patients (16.3%) and was mostly located in the anterior pericardium at low amounts. The serum levels of high-sensitive C-reaction protein before PCI and troponin T in the group with PE after PCI were significantly higher than those in the group without PE (p < 0.0001). The presence of PE was associated with the procedural time (OR = 1.02, p = 0.035) and the degree of interventional complexity (multiple vessels OR = 1.89, p = 0.014; chronic total occlusion OR = 2.04, p = 0.005; and PCI with rotational atherectomy OR = 1.15, p = 0.011) independent of the number of culprit vessels and stents. During 1-year follow-up, a significantly higher number of cardiac deaths (3) and myocardial infarctions (8) occurred in patients with PE than in patients without PE (P < 0.05). Conclusion: Post-PCI acute PE was frequent, generally mild, mainly asymptomatic, and independently associated with procedural time and complexity. This effusion, which is considered as a cardiac damage marker, could be a predominant clinical sign for long-term prognosis.